STRATEGI PENGEMBANGAN AGRIBISNIS BUDIDAYA RUMPUT LAUT UNTUK MENINGKATKAN PRODUKSI DI KECEMATAN TANETE RIANTTANG KABUPATEN BONE - RAHMAWATI TAHIR; HASMIDAR HASMIDAR; ISLAWATI ISLAWATI; MURNI DJABAR (GANEC SWARA, 2024)
Seaweed is one of the fishery commodities that has great potential to be developed in coastal areas, especially in Bone Regency which is one of the producing areas of Eucheuma cottonii seaweed. From 2018 until now the demand for seaweed continues to increase while the amount of production is unstable due to several main problems such as farmers' lack of understanding of handling upstream sub-systems, empowerment of cultivation sub-systems and downstream sub-systems and the marketing system only relies on collecting traders. The purpose of this study is to describe the potential of seaweed, identify internal and external factors that influence the increase in production and determine the priority of seaweed agribusiness development strategy in Tanete Riattang District. The sampling technique uses purposive sampling with a qualitative approach using a questionnaire tool. The number of respondents was 67. Data obtained through in-depth interviews with key informants are agribusiness system actors as internal parties, namely middlemen in the upstream subsystem, seaweed farmers in the farming subsystem, collecting traders in the marketing subsystem, Fisheries Office. Furthermore, a Focus Group Discussion (FGD) was held. Then it is analyzed using SWOT analysis. The results show that opportunities for seaweed cultivation are still open, therefore the development concept is directed to realize business opportunities, improve the quality and quantity of seaweed production and create new markets to meet high demand to realize premium quality in a sustainable manner supported by oriented institutions that can compete in the local market and export markets to increase income that provides benefits for farmers in maintaining seaweed stabitlity.